Peran Putusan Pengadilan Agama Dalam Penyelesaian Sengketa Harta Bersama Setelah Perceraian - Miasiratni Miasiratni (Journal of Global Legal Review, 2025)
This study aims to analyze the role of Religious Court decisions in resolving joint property disputes after divorce, and to assess the extent to which the decision provides justice and legal certainty for the parties. The method used in this study is an empirical approach, with a case study at the Padang Religious Court. Data were obtained through a study of court decision documents, interviews with judges, and observations of the trial process and implementation of decisions. The results of the study indicate that Religious Court decisions have an important role in resolving joint property disputes, but there are still obstacles in their implementation, such as a lack of legal understanding from the parties, administrative obstacles, and limitations in the execution mechanism. Most decisions have considered the principles of justice and proportionality in the division of property, therefore, strengthening is needed in the aspects of legal socialization and the effectiveness of the implementation of decisions to ensure the protection of the rights of the parties after divorce.